Marcos que limitam espaços que agregam : os reflexos das lutas emancipatórias das colônias hispânicas e a fronteira oeste de Mato Grosso (1821-1831) - Soares, Maria do Socorro Castro (2015)
ABSTRACT: The object of study in this thesis is the attempt to annexation the high Peruvian Province of Chiquitos to the Brazilian Empire, in the historical context of the First Brazilian Empire (1821-1831). The pivotal point of this object is the Brazilian western border. In this paper, it’s understood as dynamic spatiality and, therefore, promoter of various relationships between Brazilians and people of Hispanic neighboring provinces. As the locus of these relationships it’s wanted to understand the Province of Mato Grosso and the high land neighboring Peruvian, with the finality to know the basis on which these relations were based, that reached jeopardize diplomatic relations between the Brazilian Empire and the Revolutionary Forces of the Simon Bolivar’s Liberator Army. It’s wanted to give visibility to the tactics and confrontations that were articulated by Mato Grosso elites, which enabled the duality of governments, putting on opposite sides of the main urban centers of the province: Vila Bela of the Trinity (legal capital) and Cuiaba (captaincy’s pioneer city). From the setting of this duality, it is possible to translate embodied tricks for institutional elements or not, overlapping the conflicting relations of the construction of political power established in Mato Grosso, in the first decades of the eight hundred. Concomitant political instability that the Province of Mato Grosso was passing by, this paper also gives special attention to the emancipation struggles of neighboring provinces and the consequences felt in the Brazilian western border.